The objects and textures of everyday life in imperial Britain
1 online resource
Keywords: "Focusing on everyday life in nineteenth-century Britain and its imperial possessions--from preparing tea to cleaning the kitchen, from packing for imperial adventures to arranging home decor--the essays in this collection analyze the idiosyncratic and ideological contours of materiality, thus demonstrating how the use of nitty-gritty elements influenced the ways that tenets of domesticity were established as central to individual happiness, national security, and imperial hegemony"--Provided by publisher.